A importância da família na educação infantil: um estudo de caso na EMEI Irmã Dulce - MELO, Marinune dos Anjos (2021)
The objective of this work is to discuss the importance of School-Family Integration in the process of teaching learning in order to achieve a quality education, since it is in the home that the child experiences the first social contact of his life, living with his family and loved ones, it can also be observed that with the presence of the family in the school context, it can help in the learning process of the child. Having as main objectives, to understand how the participation of the family occurs in the school learning of the child, verifying the participation of the family in the school life of the children; identifying how families participate in children's school life; investigating whether in the School's Political Pedagogical Project there is concern about the relationship with the Family. Considering that the family constitutes the dynamic unity of affective, social and cognitive relations that are immersed in the material conditions. It is well known that in order to have a good practice it is necessary for the teacher to keep up-to-date, researching and studying, since students need solutions to the problems of their current teaching, during the stage of the internship they were moments rich and important lived in a context in the classroom, making a dialectical relationship between theory and practice. Also during the construction of this work in field research, dynamic and pleasurable activities were developed, encouraging parents to participate more in the teaching and learning process through play activities, providing parents with various educational strategies, sometimes challenging, in order to understand better each, respecting the limits.